2016
DOI: 10.1111/1471-0528.14390
|View full text |Cite
|
Sign up to set email alerts
|

Why do lactobacilli dominate the human vaginal microbiota?

Abstract: Lactobacilli prevent infection without inducing inflammation to maximise fertility and pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
175
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(189 citation statements)
references
References 58 publications
8
175
1
5
Order By: Relevance
“…in the lower reproductive tract is well described and can be partly attributed to lactic acid‐driven acidification of the vagina, which inhibits growth and colonisation of other pathogenic species . Furthermore, lactic acid can suppress production of inflammatory mediators in the vagina . Data from our cohort allow us to conclude that the protective role of Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 66%
“…in the lower reproductive tract is well described and can be partly attributed to lactic acid‐driven acidification of the vagina, which inhibits growth and colonisation of other pathogenic species . Furthermore, lactic acid can suppress production of inflammatory mediators in the vagina . Data from our cohort allow us to conclude that the protective role of Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 66%
“…In our study, we observed that L. crispatus (99%)/ L. acidophilus (99%) at early gestation may be associated with decreased risk of spontaneous preterm birth, which is similar to recent findings from two UK studies (in predominantly white populations) and a study consisting of two cohorts of white and African American women . Among other lactobacilli, L. crispatus has the largest genome, and potential bacteriocin and adhesin genes . Stafford et al, recently reported a positive association between L. crispatus and succinate levels.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacilli dominate the vaginal microbiome in the majority of reproductive-age women (38), but not in any other mammal, including nonhuman primates (39,40). The evolution of Lactobacillus dominance in humans may have been a response to the unique sexual behavior of humans and the need to prevent genital tract infections that interfere with fertility and pregnancy (40). Lactobacilli kill vaginal pathogens, including C. trachomatis (41).…”
Section: Trachomatis Persistencementioning
confidence: 99%